Perancangan Interior Fasilitas Sensori Edutainment di Semarang - Elizabeth Gina Mitayanny; Hedy Constancia Indrani; Grace Setiati Kattu (Intra, 2019)
Child’s education consisted of two aspects, formal which is in school and informal in education center. Edutainment center is a place where children can study and play simultaneously. The importance of sensory and motoric stimulation to children in younger ages will influence their growth in personal and social skill, whether in school and outside’s school, even affecting their further development in their upcoming life. Sensory education center is designed for children with age range from 3 to 12 years old, which is classified as Golden Age. This design will be divided into 3 stages, starting from understanding, designing, and detailing. Every stage will be applied with Bryan Lawson’s Method, where it will be divided into analysis, evaluation, and synthesis phase to produce design final and another related product.